2016
DOI: 10.1007/s00464-016-5291-1
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted colorectal surgery in obese patients: a case-matched series

Abstract: There is no difference in conversion to laparotomy and overall complication rates in non-obese and obese patients undergoing robotic-assisted colorectal surgery. However, obesity is associated with a higher prevalence of wound complications. Robotic-assisted surgery may minimize conversion to laparotomy and complications typically seen in obese patients due to improved visualization, instrumentation, and ergonomics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 29 publications
1
47
0
Order By: Relevance
“…The reasons might be associated with that, the robotic system was more complicated and needed more time to install the procedures in general. [35] Furthermore, due to lack of haptic feedback and remote operation, surgeons had to take more time to complete regular tasks during robotic procedure. The experience of surgeons might be a significant factor contributing to the difference of operative time for RTME.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons might be associated with that, the robotic system was more complicated and needed more time to install the procedures in general. [35] Furthermore, due to lack of haptic feedback and remote operation, surgeons had to take more time to complete regular tasks during robotic procedure. The experience of surgeons might be a significant factor contributing to the difference of operative time for RTME.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is still a subject of debate, with numerous studies demonstrating no difference in short-term outcomes between laparoscopic obese and non-obese colorectal surgery patients [30, 31]. Nevertheless, the role of robotic colorectal surgery in obese patients has only been investigated in a handful of studies [9, 18, 19, 32, 33], with only two comparing the outcomes of obese robotic vs laparoscopic rectal surgery patients [18, 19]. The remaining three studies compared the outcomes of obese versus non-obese patients receiving robotic rectal surgery, with all three studies demonstrating no difference in short-term outcomes between obese and non-obese patients [9, 32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…There is consensus amongst surgeons that obesity increases the technical difficulty of colorectal surgery [7, 8]. Obese patients tend to have a thickened and excessive omentum and mesentery which restricts the space for instrumental manoeuvre, limits access and vision, distorts the surgical planes and can lead to problematic bleeding [9]. With obesity becoming increasingly a major hazard to public health worldwide, colorectal surgeons are likely to encounter and operate on this group of patients in increasing numbers [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…While robotic colorectal surgery has been proven to be generally safe in individuals with obesity, studies have shown that patients with obesity have a significantly higher prevalence of wound complications 10. Additionally, Haas et al showed that patients with morbid obesity undergoing minimally invasive colorectal surgery (conventional laparoscopic and robotic) have significantly longer operative times and increased blood loss during procedures 11.…”
Section: Discussionmentioning
confidence: 99%